DATA REVOLUTION IN THE RETAIL SECTOR – SOCIOTECHNICAL IMAGINARIES OF AUTONOMOUS STORE - Pereira, J.; Viseu, A.; Delicado, Ana; Vicente, P. N. (8º Encontro Anual de Economia Política, 2025)
‘Autonomous stores’ are often characterized in the media as the future of shopping: smart physical environments augmented through digital technologies (Viseu 2003) that can process data automatically, seamlessly, and without the need for workers, identifying both consumers and their actions. References to autonomy and automation conjure a set of imaginaries of technology in the service of innovation and progress: for consumers these novel environments are purported to mean gains in convenience, whereby saving time is saving money. For retailers, they mean the possibility of gathering significant amounts of information on the behaviour of the customers in a store environment, thus being another manifestation of what Zuboff (2019) calls ‘Surveillance Capitalism’. Despite being hailed as autonomous, these spaces are vast digital assemblages that rely upon networked infrastructures composed of people, knowledges, and numerous technological entities (such as, AI, sensors, algorithms, computer vision, cameras). Portugal is one of the leaders in this future-making endeavour: in 2019, SENSEI, a Portuguese “unicorn” specialized in the development of autonomous stores technologies, partnered with SONAE, one of the largest Portuguese retail chains, to open ‘Continente Labs’ an autonomous store in Lisbon. This paper draws upon a thematic analysis of data generated from a media analysis of Portuguese and international newspaper and magazine articles from 2016 until 2023 (which also includes opinion and paid content). We pay particular attention to the discourses through which they are built: Who is pushing for them? Why? What are the main issues that are being discussed both in terms of advantages and problems? Who is included/excluded? And, finally, what futures are being built? This will then allow us to shed light on the concepts that underlie these spaces – What are “autonomy” and “smartness” in autonomous stores?